(untitled) (Al-Academy, 2017)
The two researchers selected the problem of research which represented with the following asking: Does the use of the shape of Round house strategy have effectiveness in the collection of students of the Department of Art Education of the subjectof teaching methods?The research aims to "measure the effectiveness of Strategy shape of Round house in the collection of students of the Department of Art Education for the material teaching methods" and to verify the aim of the research two zeroassumptions was identified to measure the level of achievement in the subject of teaching methods of third stage students in the Department of Art Education –College of Fine Arts.The research community included the students of Art Education Department / College of Fine Arts at Baghdad University who are studying the subject of teaching methods to be within the vocabulary curriculum of Technical Education Department and totaling 60 students, divided into (4) classes. The researchers choose a sample of research randomly from the students of third stage of the Department of Technical Education and for both sexes, were selected (10) students who are studying the subject of teaching methods under a strategy of shape of Roundhouse. The researchers used the experimental design with partial settings (oneexperimental group) to verify that the objectives of the research and of detection effectiveness Strategy of shape of Round house in the collection of students of the Department of Art Education for the subject of teaching methods for the purpose of achieving the objectives of the research and the assumptions it was necessary to create the search requirements, which is to define educational subject taught during the application of research and experience to determine the educational goals to refer thus to behavioral objectives